PENDAMPINGAN IBU BALITA DALAM INOVASI PEMBUATAN DAN PEMBERIAN MAKANAN TAMBAHAN PADA BALITA DENGAN BAHAN KEARIFAN LOKAL - Dwi Siska; Rita Agustiningrum; Esti Dwi; Iffah Elfrida; Siti Cholifah (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2025)
Stunting is a chronic malnutrition probleim causeid by insufficieint nutritional intakei for a long timei duei to feieiding that is not in accordancei with nutritional neieids. Stunting can occur from thei timei thei feitus is still in thei womb and only appeiars whein thei child is two yeiars old (Ministry of Heialth of thei Reipublic of Indoneisia, 2016), this reisults in disruption of child growth If not handled properly, it risks disrupting the child's physical and cognitive development, so that it can have an impact on the child's life until adulthood, making nuggets and shredded kupang is a healthy menu designed as a home-cooked menu and toddler food which is a new attraction to prevent stunting in alternative KKN activities carried out in Balong gabus village, temple sub-district, Sidoarjo Regency. After the implementation of the toddler class with the method of providing pmt innovation education, how to make kupang nuggets and shredded kupang and providing a healthy menu, so that mothers can process kupang properly and healthily. With this program presented, it is hoped that it can have a good impact on preventing or improving the quality of nutritional status in stunting toddlers in Balonggabus Village, Candi District, Sidoarjo Regency.